Effect of halloysite nanotubes on morphology and mechanical properties of alkali treated pineapple fiber reinforced epoxy composites. (2021) - Suresha, B.; Hemanth, G.
Abstract: Present study deals the surface morphology and mechanical properties of alkali treated pineapple fiber reinforced epoxy (PF/Ep) composite with and without halloysite nanotubes (HNTs). The loading of HNTs are 1, 3 and 5 wt. % in PF/Ep composite. PF/Ep and HNTs filled PF/Ep composites were characterized in terms of measured density, morphology, tensile and flexural properties. Mechanical test results revealed that incorporation of the HNTs augmented the tensile and flexural properties. Alkali treated PF/Ep composite with 3 wt. % HNTs showed 16% and 22% increase in tensile strength and Young's modulus respectively and 23.01% and 29.96% in flexural strength and flexural modulus relative to unfilled alkali treated PF/Ep composites. Overall we concluded that alkali treated PF with 3 wt. % HNTs effectively improved the morphological and the mechanical properties of epoxy for various engineered and futuristic applications.